2019
DOI: 10.1111/vde.12811
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial efficacy of two medical grade honey formulations against common high‐risk meticillin‐resistant staphylococci and Pseudomonas spp. pathogens

Abstract: Background Antimicrobial resistance is a problem in human and animal healthcare. Honey may be used for its wound healing properties and antimicrobial effects. Objective To investigate the antimicrobial activity of two commercially available medical grade honeys (MGHs) against Staphylococcus spp. and Pseudomonas spp. isolates. Methods and materials Two formulations, MGH1 (40% w/v honey) and MGH2 (80% w/v Manuka honey), were tested in vitro for minimal inhibitory concentrations (MIC) and minimal bactericidal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 45 publications
0
41
0
3
Order By: Relevance
“…A direct in vitro comparison study of L-Mesitran Soft and Medihoney against multiple (antibiotic-resistant) strains of staphylococci and Pseudomonas spp. pathogens showed that L-Mesitran had a more robust antimicrobial activity, despite containing half the concentration of honey [ 11 ]. This may have been caused by the difference in the type of honey, as there can be a 100-fold difference in antimicrobial activity between honey types [ 26 ]; alternatively, it may have been caused by the supplements added to L-Mesitran Soft [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A direct in vitro comparison study of L-Mesitran Soft and Medihoney against multiple (antibiotic-resistant) strains of staphylococci and Pseudomonas spp. pathogens showed that L-Mesitran had a more robust antimicrobial activity, despite containing half the concentration of honey [ 11 ]. This may have been caused by the difference in the type of honey, as there can be a 100-fold difference in antimicrobial activity between honey types [ 26 ]; alternatively, it may have been caused by the supplements added to L-Mesitran Soft [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…pathogens showed that L-Mesitran had a more robust antimicrobial activity, despite containing half the concentration of honey [ 11 ]. This may have been caused by the difference in the type of honey, as there can be a 100-fold difference in antimicrobial activity between honey types [ 26 ]; alternatively, it may have been caused by the supplements added to L-Mesitran Soft [ 11 ]. Other studies demonstrated that L-Mesitran Soft has a stronger antimicrobial activity than its raw honey, which supports that the supplements added to the formulation, such as vitamins C and E, enhance the antimicrobial activity [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that the supplements in L-Mesitran enhance the antimicrobial properties of its raw honey 20,21 and is more potent than Manuka-based Medihoney. 22…”
Section: Methodsmentioning
confidence: 99%
“…A range of inhibition can be observed for both Manuka honey and medical-grade honey against a variety of Staphylococcus aureus isolates, with all MICs being 20% or less [31][32][33]35,[37][38][39][40][41][42]45,46]. For Manuka honey, the Comvita Manuka 5+ exhibited the lowest MIC for almost all Manuka honey types tested against S. aureus ( Figure 1A).…”
Section: The Impact Of Honey On Staphylococcus Aureusmentioning
confidence: 98%